Synthesis of Porous Carbon Materials by the Replication of Organoclays - Tien Thao, Nguyen; Thi Hien, Pham (Asian Journal of Chemistry, 2013)
Di Linh (Vietnam) clay was chemically treated and modified by cetyltrimethylammonium bromide to prepare the organoclays with high interlayer spacings. The organoclay samples are further used as the hard template for the synthesis of porous carbon materials. The removal of clay template yield porous carbon materials having a moderate surface area (80-290 m2/g), micro- and mesoporous structure. The morphology of the carbon products is well correlated with the characteristic properties of clay templates. The unpillared clays lead to the formation of carbon nanoparticles with rather high large surface area and more porosity while organoclays gives carbon nanosheets and the medium specific surface area.